(untitled) (Research, Society and Development, 2021)
This study proposes a review of biological potential of cinnamon (Cinnamomum cassia) essential oil with a focus on microencapsulation as an alternative to control the occurrence of pests in stored maize grains. Due to the demands on corn productivity, there is the need to improve grain storage processes and conditions, since that in this stage there are quantitative and/or qualitative losses, mainly due to the maize weevils (Sitophilus zeamais) and the incidence of mycotoxin-producing fungi (Penicillium crustosum, Alternaria alternata and Aspergillus flavus). The control of these pests is usually carried out with chemical insecticides, which can leave toxic residues in the grain. Therefore, the microencapsulation of essential oils appears as a promising alternative, considering the volatility of aromatic compounds, which are largely responsible for the activity against pests.